2021
DOI: 10.1002/kin.21503
|View full text |Cite
|
Sign up to set email alerts
|

Observation of low‐temperature chemistry products in laminar premixed low‐pressure flames by molecular‐beam mass spectrometry

Abstract: The formation of typical low‐temperature oxidation products is observed in laminar premixed low‐pressure flames investigated by photoionization molecular‐beam mass spectrometry at the Swiss Light Source. The C1–C4 alkyl hydroperoxides can be identified in n‐butane‐ and 2‐butene‐doped hydrogen flames by their photoionization efficiency spectra at m/z 48, 62, 76, and 90. C1–C3 alkyl hydroperoxides are also observed in a propane‐doped hydrogen flame and in a neat propane flame. In addition, threshold photoelectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 79 publications
2
13
0
Order By: Relevance
“…For the first time, Bierkandt et al have detected the methylperoxy (H 3 C-OO) radical in a flame (Figure ). Both the photoionization spectrum and the photoelectron spectrum clearly show the presence of this radical (Figure ). Larger alkylperoxy radicals were not detected, but the absence of a mass spectrometric signal does not exclude their presence in the flame.…”
Section: Clean Combustionsupporting
confidence: 74%
See 4 more Smart Citations
“…For the first time, Bierkandt et al have detected the methylperoxy (H 3 C-OO) radical in a flame (Figure ). Both the photoionization spectrum and the photoelectron spectrum clearly show the presence of this radical (Figure ). Larger alkylperoxy radicals were not detected, but the absence of a mass spectrometric signal does not exclude their presence in the flame.…”
Section: Clean Combustionsupporting
confidence: 74%
“…Formation of alkyl hydroperoxides in flames was first observed by Zhang et al by photoionization mass spectrometry, but the corresponding radicals remained elusive until recently . Bierkandt et al investigated the low-temperature oxidation in different flames and found compelling evidence for peroxy radical species …”
Section: Clean Combustionsupporting
confidence: 59%
See 3 more Smart Citations